PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR KPK DAN FPB DI KELAS V SD - Septirasih, Septirasih; Zainil, Melva; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the effect of  Problem Based Learning model to KPK and FPB learning outcomes in grade V SD. The type of this research is quasi experiment with nonequivalent control group design. The sample of research is students of class VB and VC SDN 23 Marapalam city of Padang. Sampling using purporsive sampling technique. The instrument used is an objective test in the form of multiple choice. Data analysis technique using t-test. The result of research shows that there is influence of Problem Based Learning model to KPK and FPB learning outcomes in primary school. This is evidenced by the t-test results on the real level α = 0.05 and dk = 58 obtained tcount (4,789)> ttable (2.002). This result shows KPK and FPB learning result of the two classes differ significantly. The average score of experimental classrooms applying the learning with the Problem Based Learning model is 80.83 higher than the class control that apply conventional learning is 70.17.  Keywords: Problem Based Learning model, learning outcomes.